2016
DOI: 10.1016/j.marpolbul.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects of the Deepwater Horizon oil spill: A review

Abstract: The Deepwater Horizon oil spill constituted an ecosystem-level injury in the northern Gulf of Mexico. Much oil spread at 1100-1300m depth, contaminating and affecting deepwater habitats. Factors such as oil-biodegradation, ocean currents and response measures (dispersants, burning) reduced coastal oiling. Still, >2100km of shoreline and many coastal habitats were affected. Research demonstrates that oiling caused a wide range of biological effects, although worst-case impact scenarios did not materialize. Biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
263
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 621 publications
(272 citation statements)
references
References 292 publications
(323 reference statements)
4
263
0
5
Order By: Relevance
“…The Gulf of Mexico not only supports a rich biodiversity of both national and global importance [10], but also delivers invaluable ecosystem services such as productive fisheries, storm protection, flood-risk reduction, water quality enhancement, faunal support, and carbon sequestration. Injury and death rates were documented for species of dolphins, sperm whales, manatees, sea turtles, mangroves, sea birds (pelicans), oysters, marine vertebrates, fish,- including shark, tuna, and shellfish-, and seaweed [9–13]). Species that surface for air such as dolphins, whales, and sea turtles showed elevated rates of stranding [10].…”
Section: Ecosystem Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gulf of Mexico not only supports a rich biodiversity of both national and global importance [10], but also delivers invaluable ecosystem services such as productive fisheries, storm protection, flood-risk reduction, water quality enhancement, faunal support, and carbon sequestration. Injury and death rates were documented for species of dolphins, sperm whales, manatees, sea turtles, mangroves, sea birds (pelicans), oysters, marine vertebrates, fish,- including shark, tuna, and shellfish-, and seaweed [9–13]). Species that surface for air such as dolphins, whales, and sea turtles showed elevated rates of stranding [10].…”
Section: Ecosystem Effectsmentioning
confidence: 99%
“…Species that surface for air such as dolphins, whales, and sea turtles showed elevated rates of stranding [10]. Disease rates among these species increased, among those lethal lung disease and primary bacterial pneumonia in bottlenose dolphins [10, 13]. Bottlenose dolphins from Barataria Bay had mortality rates 8% higher than, and reproductive success rates 63% lower than, reference (not oiled) areas [12, 13].…”
Section: Ecosystem Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental distribution of the oil throughout the GoM has been significant. Shoreline assessment teams indicated that between 1,773 and 2,100 km of shoreline was affected by the oil spill (Michel et al, 2013;Beyer et al, 2016), and two years after the spill, oil was still present on 687 km of shoreline (Michel et al, 2013). Moreover, the crude oil, and associated polycyclic aromatic hydrocarbons (PAH), was detected in the sediment directly and 1.5 years after the spill (Kirman et al, 2016;Turner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies are been made to understand the potential harm to marine environment caused by Offshore Oil and Gas operations and to learn important lessons from catastrophic occurrences (BEYER et al, 2016;WHITE AND BERRY, 2014).…”
Section: Introductionmentioning
confidence: 99%